Placebo and nocebo - Luana Colloca (Pathos, 2009)
Over the past two decades the placebo and nocebo effect has shifted from being a nuisance in clinical research to a promising model of an emerging neuroscience of mind-brain-body interactions. In fact, the interest in and the success of placebo research resides in its multifaceted meaning, which involves key issues in modern science - from neurobiology to philosophy, from ethics to social psychology, and from clinical trials design to medical practice. Thus, the placebo effect, which has long been neglected by the neuroscience community, is today considered a real and detectable biological phenomenon, and the question of whether placebos work has been reframed as to how they work. The aim of this review is to introduce the reader to the nature and extent of the placebo and nocebo phenomenon and to present the interesting implications of the new evidence that arises from recent research in the field of pain.